Peranan Guru PAI Dalam Penanaman Nilai-Nilai Karakter Islami Melalui Pembiasaan Pada Siswa SMP Negeri 10 Mukomuko - Bengkulu - Samsul Hadi (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2022)
The purpose of this study is to describe the role of Islamic religious education teachers in instilling Islamic character values ??through habituation to students at SMPN 10 Mukomuko. And to describe the factors that hinder Islamic religious education teachers in instilling Islamic character values ??through habituation in junior high school students. This research uses field research methods using a qualitative descriptive approach. The result of the research is the role of Islamic religious education teachers in instilling Islamic character values ??through habituation in junior high school students, namely (1) Teachers as educators. (2) The teacher as a guide. (3) The teacher as a model and role model. (4) Teachers as advisors. The factors that hinder the Islamic Religious Education teacher in instilling Islamic character values ??through habituation in junior high school students, namely (1) Student background. (2) Low student interest. (3) School environment. (4) Facilities.